Convex sets strict separation in the minimax theorem - Ferreira, M. A. M.; Matos, M. C. P. (Applied Mathematical Sciences, 2014)
The convex sets strict separation is very useful to obtain mathematical optimization results. The minimax theorem, a key result in Game Theory is an example. It will be outlined in this work.